Pengujian Kualitas Sistem Informasi Pelayanan Cuti (SIMPEL-COI) DISHUB Kota Jambi Menggunakan Metode Webqual 4.0 - Ismail, Muhammad; Yulvianda, Renaldi (LPPM STIKOM Dinamika Bangsa, 2023)
The information system (website) for online leave services (SIMPEL-COI) is a form of service within agencies created by the Jambi City Transportation Service to make it easier for employees to take leave without the need to go through a long process (implementation, management, calculation and replacement of leave) and to help parties those in the UMPEG field (general and staffing) to reduce their workload. The purpose of this study was to measure the quality of the information system for online leave services (SIMPEL-COI) using 3 dimensions of webqual 4.0 namely usability, information quality and service interaction based on user satisfaction. This is based on the problems that arise, namely the unattractive UI/UX appearance, difficulty in use and quality testing that has never been done so that the level of success and suitability based on user satisfaction is unknown. Data collection in this study was carried out using a questionnaire made via Google form with instrument measurements using a Likert scale which was distributed online for one week through communication media. The research sample used in this study was 67 respondents and processed using SPSS version 26 so that the results of the validity test, reliability test, T test, F test and R square test were obtained which became a significant reference or measurement guideline. The results of testing the dimensions used in this study, namely Usability, Information Quality, Service Interaction, have insignificant values so that it can be said that they do not have good quality because user satisfaction has not been fulfilled with a percentage of 0.05%.